2015
DOI: 10.1371/journal.pone.0138267
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analyses of the Biological Effects of Airborne PM2.5 Exposure on Human Bronchial Epithelial Cells

Abstract: Epidemiological studies have associated high levels of airborne particulate matter (PM) with increased respiratory diseases. In order to investigate the mechanisms of air pollution-induced lung toxicity in humans, human bronchial epithelial cells (16HBE) were exposed to various concentrations of particles smaller than 2.5 μm (PM2.5) collected from Beijing, China. After observing that PM2.5 decreased cell viability in a dose-dependent manner, we first used Illumina RNA-seq to identify genes and pathways that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 42 publications
(46 reference statements)
1
57
1
2
Order By: Relevance
“…Additionally, many in vitro studies have focused on the upregulation and release of proinflammatory cytokines, such as IL1B, IL6, CXCL8 and TNF, by airway epithelial cells in response to PM2.5 exposure due to the critical role of these cytokines in the initiation and resolution of inflammation. [4][5][6] In fact, elevation of these cytokines has also been observed in the bronchial alveolar lavage fluid of animals, 28 further confirming the results obtained from the in vitro studies. In this work, to explore the inflammatory responses induced by the particles, the expression levels of several inflammatory factors were analyzed.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Additionally, many in vitro studies have focused on the upregulation and release of proinflammatory cytokines, such as IL1B, IL6, CXCL8 and TNF, by airway epithelial cells in response to PM2.5 exposure due to the critical role of these cytokines in the initiation and resolution of inflammation. [4][5][6] In fact, elevation of these cytokines has also been observed in the bronchial alveolar lavage fluid of animals, 28 further confirming the results obtained from the in vitro studies. In this work, to explore the inflammatory responses induced by the particles, the expression levels of several inflammatory factors were analyzed.…”
Section: Discussionsupporting
confidence: 70%
“…The release of these molecules then facilitates a pulmonary inflammatory response within a short time, which exacerbates the airway symptoms, especially in vulnerable populations with preexisting cardiopulmonary diseases and the elderly. 2,[4][5][6] When the response is sustained for a longer period, proinflammatory factors may move to the systemic circulation from the lungs and then cause adverse effects on the cardiovascular system. 2,3,6 Therefore, control of the inflammatory response may allow for more effective strategies to abate the cardiopulmonary dysfunctions induced by PM2.5.…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental and observational studies demonstrate the capacity of NO 2 along with other air pollutants to activate oxidant pathways through formation of ROS, triggering inflammation and cell death (Lodovici and Bigagli 2011). Studies in human bronchial epithelial cells showed differential expression of genes involved in response to oxidative stress following air pollution exposure (Rossner et al 2015; Zhou et al 2015). In our study we observed differential methylation in CAT and TPO .…”
Section: Discussionmentioning
confidence: 99%
“…When HBEC, derived from immortalized cell lines or normal donors, are exposed to ambient PM or DEPs, a strong up‐regulation of different epithelial cytokines can be observed. The levels of IL‐6, IL‐8 and TNF‐α, for instance, were significantly increased in cells that were exposed to PM. Of note, also MIP‐3α/CCL20, an important chemokine involved in DC recruitment, was increased in HBEC upon ambient PM exposure.…”
Section: Air Pollution and Asthmamentioning
confidence: 99%
“…Importantly, after internalization or PRR activation, exposure to ambient PM/DEPs will activate oxidative stress responses in the airway epithelial cells. When lung epithelial cells are exposed to ambient PM/DEPs higher levels of intracellular ROS formation, activation of oxidative stress‐responsive genes, such as HMOX1, and oxidative damage has been demonstrated . Ambient PM/DEPs exposure was further associated with the overexpression of several genes and increased phosphorylated proteins related to the MAPK or PI3K/AKT pathway .…”
Section: Air Pollution and The Airway Epitheliummentioning
confidence: 99%